The The Representation of Mothers as Bearers of Culture in Three Short Stories from Indonesia - Esther Deborah Kalauserang (NOTION: Journal of Linguistics, Literature, and Culture, 2023)
Mothers occupy an important place in the smallest scale of the society, namely, the family. Therefore, the purpose of this research is to examine the representation of mothers as bearers of culture from three Indonesian short stories by finding out: 1) how the Indonesian mothers are portrayed in the three short stories; and, 2) how the Indonesian mothers in the three short stories are portrayed as bearers of culture. The approach employed in this research is literary descriptive analysis while applying the theory of motherhood and culture to answer the first and second research objective. The result shows that the Indonesian mothers are portrayed as individuals who are self-sacrificing, and those with the capacity to act as a bridge between individuals. Furthermore, the Indonesian mothers are portrayed as bearers of culture through their association with the process of baby-naming in accordance with their cultural identity, through their process of traditional or religious burial rites, and through language.